PENGARUH OPINI AUDIT, PERGANTIAN AUDITOR DAN KEAHLIAN KOMITE AUDIT TERHADAP AUDIT DELAY - Sutarti, Sutarti; Rahman, Kristanti; H, Hayaturokhmah (JURNAL EKONOMI, 2024)
This study aims to analyze the effect of Audit Opinion, Auditor Change and Audit Committee Expertise on Audit Delay, in LQ45 companies listed on the Indonesia Stock Exchange 2018-2020 period. The type of data used is secondary data taken from the website www.idx.com. The sample in this study were LQ45 companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used purposive sampling. This type of research is quantitative using SPSS Version 25. The results showed that Audit Opinion has an effect on Audit Delay, while Auditor Change and Audit Committee Expertise have no effect on Audit Delay